Capturing Arab gulf market: an analysis of Malaysian exports competitiveness in the market - Abu-Hussin, M.F.; Sulaiman, A.A.; Hussin, M.Y.M. (2011)
In recent years, the Arab Gulf Countries in particular Gulf Cooperation Council (GCC) has been an attractive market destination for the Asian businesses. China, India, Japan and other Asian countries have huge interest in developing close relationships with the six nations. As an emerging economy in the West Eastern Asia, the GCC offer huge interest in doing businesses and become a gate for the Middle Eastern markets. Malaysia, besides the religious affinity that it shares with the Arab Gulf Countries, is also highly interested in expanding its trade relations with the Arab Gulf Economies.Therefore, in this article, an investigation on the countries’ trade compositions and followed by a study on Exports competitiveness were conducted. Finding from the analysis of exports competitiveness of Malaysian products will then be compared to the major Asian exporters in the GCC market. By doing this, it will identify Malaysia’s niche product that could potentially expanded in this market. This will shed a light on the Malaysia’s willingness to enhance market penetration to this economic bloc.